Weight gain in pregnancy: can metformin steady the scales?. (12th December 2022) - Adams, Jacquelyn H.; Poehlmann, John; Racine, Jenna L.; Iruretagoyena, J. Igor; Eddy, April; Hoppe, Kara K.; Stewart, Katharina; Rhoades, Janine; Antony, Kathleen M.
Abstract: Objective: Metformin has been associated with modest weight reduction in the non-pregnant population. Our hypothesis is that metformin exposure will lead to a higher incidence of appropriate weight gain during pregnancy. Study Design: This was a retrospective cohort study in a single center between 2009 and 2019. We included all pregnant women with type 2 diabetes or prediabetes. We compared women exposed to metformin in any trimester. The primary outcome was appropriate weight gain defined by the Institute of Medicine guidelines. Secondary outcomes included excessive weight gain, weight loss, suspected fetal growth restriction (FGR), and mean birth weight. Adjusted odds ratios or group differences were calculated using logistic or linear regression, controlling for confounders. Results: Of 41, 472 deliveries during the study period, 511 pregnancies met inclusion criteria. 284 pregnancies had no metformin exposure; 227 did have metformin exposure, of which 169 (72.2%) were initiated on metformin in the first trimester. Women exposed to metformin in any trimester were statistically not more likely to have appropriate weight gain (aOR 1.53 (95% CI 1.00–2.34, p = .048), but did have less excess weight gain (aOR 0.45, 95% CI 0.30–0.66, p < .001), and more maternal weight loss (aOR 2.17, 95% CI 1.18–3.98, p = .012) than the unexposed group. Women exposed to metformin in the first trimester of pregnancy were less likely to have excess weight gain (aOR 0.39, 95% CI 0.25–0.61, p < .001) and more likely to have maternal weight loss (aOR 2.56, 95% CI 1.30–5.07, p = .007) than the unexposed cohort. There was no difference in FGR (5.3% vs 2.5% p = .094) or mean birth weight (3235.6 vs 3352.4 gm p = .122) in the metformin exposed group vs non-exposed groups, respectively. Conclusions: Metformin exposure in pregnancy was associated with less excess weight gain and a higher rate of weight loss. There was no difference in FGR or mean birth weight in metformin exposed neonates. This suggests that metformin may help avoid excess weight gain and its associated comorbidities.